Customer satisfaction on services quality of KTMB: A study among STML students - Tan, Hooi Yee; Ahmad, Azhar (Universiti Utara Malaysia, 2020)
Keretapi Tanah Melayu Berhad (KTMB) is the main rail operator in Peninsular Malaysia. Nowadays, rail transportation becomes a trend that many human beings will choose to take the train. This is because taking the train is very convenient and also can help in cost saving. Thus, in this research paper, the researcher will provide and present a further understanding of the KTMB services in the Northern sector. Besides that, the researcher will survey the satisfaction on service quality of KTMB among STML students. SERVQUAL model is used in this survey in order to survey about the satisfaction on service quality.